ISLAMIC EDUCATION ANOMALIES: Critical Study of The Educations Practice Recently - Shobrun Jamil (CV. Amerta Media, 2023)
This paper issued to know some anomalies that lies in the islamic education practice recently. Espesially the moral code or akhlak that brooked by the education doer or perpetrator such as the teacher and the student. Anomaly is defined as a deviation from the common rule, type, arrangement, or form. Anomaly also called the angle between the periapsis of an orbit and the position, that taken from Greek language as anomalia. This paper was wroten based on the information from some newspapers or the televitions that show that anomalies happen in the Islamic education practices, such as the teacher that bullied by the student that happen on Yogyakarta province recently and the other regions of Indonesia or the bad behavioral of the students light begin from the free sex, drugs, or any amoral actions that apllied by them. Of course these penomenons carry out ourselfes to seek the reason why these was happened. We have to discuse to apllied the moral conduct again and again to minimilize the wrong acts, and the writter see that is originated from the moral education have to strange in the scholls. Many anomalies that occur in education worlds besides of the moral students is the teacher behavior that arranges them to apllied the bad behavior also like the miss of honesty that caused by National Exam or the other examinations in their schools. Some theachers has mental pressure caused of the examination that carries them to do the dishonesty. So the moral or ethics must be strengthened in the education lessons in the schools.